Pewarnaan Titik r-Dinamis pada Graf Hasil Operasi Edge Corona - Adelia Putri Liowardani; Dafik Dafik; Arif Fatahillah (jcgant, 2020)
This research is a development of research on r-dynamic vertex coloring on simple, connected, and undirected graphs. The rdynamic vertex coloring on the graph G is the r point coloring of the r graph so that the vertices of degree two on the G graph have at least two different color neighbors. The r-dynamic vertex coloring is satisfied if it meets the conditions for v V(G), |c(N(v))| ≥ min{r,d(v)}. The chromatic number for the r-dynamic vertex coloring of the graph G is denoted as χ_r(G). In this study, we discuss the r-dynamic vertex coloring on the graph resulting from the edge corona operation on a path graph with a complete graph, a star graph, and a sweep graph. It is denoted that the result of the operation of edge corona graph G and graph H is G H. In this study, the results of the r-dynamic vertex coloring are described in the operation graph P_n K_m, P_n S_m, P_n P_m, and P_n B_(m,k)